Increasing translation of research evidence for optimal park design: a qualitative study with stakeholders - Jenny Veitch; Emily Denniss; Kylie Ball; Harriet Koorts; Benedicte Deforche; Anna Timperio (BMC, 2020)
Abstract Background The design of parks is critical to ensure they are appealing, meet the needs of the community and optimise opportunities for physical activity, relaxation, exposure to nature and social interaction. There is currently a lack of understanding on how research evidence is informing park design and how to reduce the many challenges associated with research-practice-policy translation. Understanding how organisations use evidence for decision-making regarding park design is critical for reducing the research-practice-policy gap and ensuring evidence based strategies inform park design to support healthy active living. This study explored stakeholder perceptions regarding factors that influence the use of research evidence to inform park planning and design, and potential strategies to enhance effective translation of research evidence for optimal park design into policy and practice. Methods One-on-one in-depth interviews were conducted with 23 stakeholders within the park design, planning and management sector. Participants shared experiences regarding: influences on park development and design; current park development policies; ways to facilitate use of evidence; and priorities for future research. Interviews were recorded and transcribed verbatim and content analysis performed using NVivo 12. Results Research evidence is used and considered important for park planning; however, several barriers were highlighted: time and cost constraints; difficulties accessing research; and limited research relevant to specific needs. Developing partnerships between researchers and park developers and providing evidence in a more accessible format such as short summaries/reports, infographics, presentations, research updates and dedicated research databases emerged as key enablers. The main research gaps identified included research into park features to encourage visitation and cost-benefit analyses studies. Conclusions This research is a first step to better understand strategies to promote more effective uptake and use of evidence to inform park planning. Researchers must develop multi-sectoral collaborations and generate policy-relevant research in a readily accessible, timely and user-friendly format to ensure evidence is used to enhance park design and ultimately public health.